Effect of Flow Rate on Hexavalent Chromium Reduction in Electroplating Wastewater Using TiO2 Immobilized Resin - Arya Darmawan; Okik Hendriyanto Cahyonugroho; Ram Babu Pachwarya (CHEESA: Chemical Engineering Research Articles, 2025)
This study aims to analyze the effect of flow rate on the reduction of hexavalent chromium (Cr6+) in electroplating wastewater treated with a TiO2-immobilized resin in a continuous fixed-bed reactor. The electroplating wastewater, characterized by Cr6+, was treated with RIPT-TiO2 functioning as a catalyst to enhance the contaminant degradation process. The flow rate was then examined to observe the effect on the reduction of Cr6+ concentration during the reaction. The results showed that increasing the flow rate within the range of 4070 mL/min affected the reduction of Cr6+, and ultimately influenced the photocatalytic efficiency. The flow rate affected the contact time between the wastewater and the catalyst. The best removal efficiency, reaching 50.83% at 180 minutes, was obtained at a lower flow rate. This study provides important contributions to the development of sustainable and efficient electroplating wastewater treatment technology using a continuous reactor system with a TiO2-immobilized resin.